2019
DOI: 10.1001/jamadermatol.2018.4231
|View full text |Cite
|
Sign up to set email alerts
|

Use of Targeted Next-Generation Sequencing to Identify Activating Hot Spot Mutations in Cherry Angiomas

Abstract: IMPORTANCE Shared gene variants in benign-malignant process pairs, such as BRAF mutations common to benign nevi and melanoma, are associated with differing phenotypic manifestations. Study of gene mechanisms underlying cherry angioma may uncover previously unknown disease relationships.OBJECTIVE To identify somatic mutations present in cherry angioma specimens by using targeted next-generation sequencing. DESIGN, SETTING, AND PARTICIPANTSIn a single-center case series, 10 formalin-fixed, paraffin-embedded cher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Multiple angiomas were significantly more frequent in patients with melanoma under 70 years old. Recently, one study has identified somatic activating mutations in GNAQ and GNA11 in a sample of cherry angiomas that also share uveal melanoma, blue nevus and melanoma associated with blue nevus 58 . In our study, the finding of cherry angiomas as a risk factor suggests that these lesions might be markers of actinic skin damage in patients with some degree of genetic susceptibility.…”
Section: Discussionsupporting
confidence: 58%
“…Multiple angiomas were significantly more frequent in patients with melanoma under 70 years old. Recently, one study has identified somatic activating mutations in GNAQ and GNA11 in a sample of cherry angiomas that also share uveal melanoma, blue nevus and melanoma associated with blue nevus 58 . In our study, the finding of cherry angiomas as a risk factor suggests that these lesions might be markers of actinic skin damage in patients with some degree of genetic susceptibility.…”
Section: Discussionsupporting
confidence: 58%
“…Congenital hemangioma of the skin (RICH and NICH), which also cluster within this group, are an exception [10]. Other neoplasms that belong to this cluster are melanocytic tumors, specifically melanocytoma, nevus of the skin, blue nevus, choroidal nevus, choroidal melanoma, and vascular tumors like congenital hemangioma, hepatic small vessel neoplasia, anastomosing hemangioma, cherry angioma, and circumscribed choroidal hemangioma [9,10,12,13,14,15,16,17,18,29,30,31,32,33]. It is common for these tumors that make up this cluster to show continuous cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…GNAQ and its paralogue GNA11 each encode an alpha subunit of a heterotrimeric G protein, a binding protein that remains in its active GTP-bound state when mutated [7,8,9]. Both genes have been reported to be mutated in several vascular malformations such as congenital hemangioma of the skin and cherry angioma and in melanocytic tumors (choroidal nevus, uveal melanoma, melanocytoma, blue nevus) [6,9,10,11,12,13,14,15,16,17,18]. Moreover, GNAQ or GNA11 mutations have been detected in several neural crest disorders such as Sturge Weber Syndrome (SWS).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the association between MM and eruptive CAs, which we arbitrarily considered to be such when there were more than 10, was highly significant in patients younger than 70 years [2]. Interestingly, the results from subsequent studies, although very heterogeneous by methodology, design and objectives, seemed to support a likely association between CAs and tumours, namely breast cancer [3] and MM [4]. A recent study found that the presence of more than 50 CAs was significantly associated with an increased risk of developing a second MM in patients with cutaneous melanoma [5].…”
Section: Introductionmentioning
confidence: 99%